Dynamical Dipole mode in heavy-ion fusion reactions in the 192Pb mass region. (March 2015) - Parascandolo, C; Pierroutsakou, D; Alba, R; Zoppo, A Del; Maiolino, C; Santonocito, D; Agodi, C; Baran, V; Boiano, A; Colonna, M; Coniglione, R; De Filippo, E; et al.
Abstract: The dynamical dipole mode was investigated in the mass region of the 192 Pb compound nucleus, by using the 40 Ca + 152 Sm and 48 Ca + 144 Sm reactions at Elab =11 and 10.1 MeV/nucleon, respectively. Both fusion-evaporation and fission events were studied simultaneously for the first time. Our results for evaporation and fission events (preliminary) show that the dynamical dipole mode survives in reactions involving heavier nuclei than those studied previously.